Evaluation of the Etest Method for Determining Voriconazole Susceptibilities of 312 Clinical Isolates of Candida Species by Using Three Different Agar Media - Pfaller, M. A. (American Society for Microbiology, 2000)
Performance of the Etest for voriconazole susceptibility testing of 312 isolates of Candida spp. was assessed against that of the National Committee for Clinical Laboratory Standards (NCCLS) microdilution broth method. The NCCLS method employed RPMI 1640 broth medium, and MICs were read after incubation for 48 h at 35°C. Etest MICs were determined with RPMI agar containing 2% glucose (RPG), Casitone agar (CAS), and antibiotic medium 3 (AM3) agar and were read after incubation for 48 h at 35°C. The Candida spp. isolates included C. albicans (n = 174), C. glabrata (n = 55), C. tropicalis (n = 31), C. parapsilosis (n = 39), C. krusei (n = 5), C. lusitaniae (n = 2), and C. guilliermondii (n = 6). The Etest results obtained using RPG correlated well with the reference MICs. Overall agreement ranged from 91% for C. glabrata to 100% for C. tropicalis, C. parapsilosis, C. guilliermondii, C. krusei, and C. lusitaniae. When CAS was used, agreement ranged from 80% for C. krusei to 100% for C. parapsilosis, C. guilliermondii, and C. lusitaniae. With AM3, agreement ranged from 58% for C. glabrata to 100% for C. lusitaniae and C. guilliermondii. The Etest method using RPG appears to be a useful method for determining voriconazole susceptibilities of Candida species.